Extensive locally invasive nasopharyngeal carcinoma involving 10 cranial nerves palsies: an interesting case report - Albilali, Abdulrazaq; Alotaibi, Naif H.; Alfadley, Abdulaziz; Alqarni, Khalid M.; Alhajlah, Abdullah (Frontiers in Oncology, 2025)
Background and objectivesCranial nerve palsies occur in approximately 20% of nasopharyngeal carcinoma (NPC) cases, often correlating with tumor location and cranial extension. This report describes a rare case involving ten unilateral cranial nerves.MethodsA 55-year-old female presented with right-sided cranial nerve palsies (II, III, IV, V, VI, VII, IX, X, XI, and XII). Imaging showed a locally invasive nasopharyngeal mass with anterior, posterior, and intracranial extension but without distant metastasis. Biopsy confirmed a poorly differentiated, non-keratinizing squamous cell carcinoma, staged as IV/A T4-N2-M0. Treatment involved concurrent chemoradiotherapy and multidisciplinary care.ResultsSix months post-treatment, there was complete recovery in cranial nerves XI and XII and near-complete recovery in nerves III, IV, and VI. Cranial nerves II, V, VII, IX, and X showed no improvement at interim follow-up.DiscussionThis case highlights an uncommon presentation of NPC with extensive cranial nerve involvement and no distant metastasis. Partial recovery of cranial nerve function following chemoradiotherapy emphasize the potential for neurological improvement in advanced NPC with comprehensive, multidisciplinary care.